Fish collection of the Universidade Federal de Rondônia: its importance to the knowledge of Amazonian fish diversity - Willian Massaharu Ohara; Luiz Jardim de Queiroz; Jansen Zuanon; Gislene Torrente-Vilara; Fabíola Gomes Vieira; Carolina da Costa Doria (Acta Scientiarum. Biological Sciences, 2015)
Biological collections preserve the biodiversity of a nation. The fish collection of the Universidade Federal de Rondônia, recently established, contains about 41% of freshwater fish species known to occur in Brazil, and 24% of South America. The biological material is distributed into 1,067 species, 21,963 lots and 149,192 specimens, gathered during five years of work. From this collection, 99% of the lots have georeferenced location, and 94% of the species were sampled in the Madeira River basin, the largest tributary in flow, drainage area and sediment discharge of the Amazonas River basin. Among the 1,008 species collected in the Madeira River basin, 80% were reviewed by Brazilian, North American and French experts, and represents the highest richness among tributaries of the Amazonas River and other rivers worldwide. Fish collection from the Madeira River basin deposited in the ichthyological collection of the Universidade Federal de Rondônia accounts for about 75% of the lots and specimens of fish from that basin available for study in collections worldwide.